Analisis jenis kalimat dalam iklan penawaran surat kabar tribun pekanbaru - Marisa Indriana; Ermawati Sulaiman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
In spoken form, sentences are spoken in an up. And down voice and loud and soft, interrupted by pauses and ending with the final intonation. While in the form of written Latin letters, sentences begin with a capital letter and end with a period (.) to state news sentences or informative ones, question marks (?) to state questions and exclamation points (!) to state imperative sentences. To describe, analyze, interpret and conclude declarative, interrogative, imperative, and interjective sentences in the advertisement offering the news paper Tribun Pekanbaru published during July 2021. The theory used is Chaer, 2009, The data source of this research is the advertisement offering the news paper Tribun Pekanbaru. This study uses aqualitative approach, this type of research is a library (Librar Research). The method used is descriptive method. Data collection techniques used are documentation techniques and hermerneutic techniques. The data analysis technique in this study makes data tables, the classified data is then analyzed, interprets, concludes there results of research on the analysis of declarative, interrogative, imperative, and interjective sentences in the advertisement of the Pekanbaru Tribune news paper offer. The results of the study based on the data analysis that there searchers did on the advertisement offerings of the Pekanbaru Tribune news paper, there searchers found 36 offer sentences that were found. 20 declarative sentences, 4interrogative sentences, 10 imperative sentences, and 2 interjective sentences